2002
DOI: 10.1002/jez.10093
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of spontaneous and heat‐induced HSP 70 expression in developing zebrafish (Danio rerio)

Abstract: A spontaneous high expression of heat shock protein 70 (HSP 70) was found to arise in zebrafish (Danio rerio) at the larval stage (84 hr after fertilization). The level of HSP 70 in 84-hr-old larvae was estimated to be six- to eightfold that of 12-hr-old embryos. As heat-induced HSP 70 synthesis in many eukaryotic organisms is known to be mediated by a transcriptional-dependent pathway activated by heat shock factor 1 (HSF-1), we then examined if the spontaneous and heat-induced HSP 70 synthesis in zebrafish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Temporal hsp70 gene expression was demonstrated for zebrafish embryos, as highest amounts of hsp70 transcript were detected at 84 h post fertilization in comparison to transcript amounts measured at 12-60 h and at 108 h post fertilization (Yeh and Hsu 2000). Later studies suggested that the spontaneous high expression of hsp70 in zebrafish embryos may be regulated via a mechanism that was different from the widely accepted HSF1/hsp70 gene transcription pathway (Yeh and Hsu 2002). Evidence towards the role and importance of different HSP70 forms is also starting to emerge as it was found that inducible hsp70 gene expression is strongly and specifically expressed within the first 38 h post fertilization only whereas the hsc70 form was sporadically detected in different zebrafish embryonic tissues (Blechinger et al 2002).…”
Section: Importance Of Hsp During Embryogenesis and Larval Developmentmentioning
confidence: 94%
“…Temporal hsp70 gene expression was demonstrated for zebrafish embryos, as highest amounts of hsp70 transcript were detected at 84 h post fertilization in comparison to transcript amounts measured at 12-60 h and at 108 h post fertilization (Yeh and Hsu 2000). Later studies suggested that the spontaneous high expression of hsp70 in zebrafish embryos may be regulated via a mechanism that was different from the widely accepted HSF1/hsp70 gene transcription pathway (Yeh and Hsu 2002). Evidence towards the role and importance of different HSP70 forms is also starting to emerge as it was found that inducible hsp70 gene expression is strongly and specifically expressed within the first 38 h post fertilization only whereas the hsc70 form was sporadically detected in different zebrafish embryonic tissues (Blechinger et al 2002).…”
Section: Importance Of Hsp During Embryogenesis and Larval Developmentmentioning
confidence: 94%
“…By contrast, untreated hsp70-Cre embryos expressed 2.9 Ϯ 2.0% of the Cre transcript levels compared with siblings heat shocked for 1 h (n ϭ 4; heat shock from 24-25 hpf at 37°C and assessed for Cre expression at 28 hpf). Thus, the hsp70 promoter can be induced by heat shock treatment; however, the promoter is active at low levels during development even in the absence of heat shock (18,19).…”
Section: Human Krasg12d Expression Can Be Induced In Transgenic Zebramentioning
confidence: 99%
“…Interestingly, in a wide range of organisms, the expression of HSP 70 has also been shown to vary during development (Dix 1997;Feder and Hofmann 1999;Giudice et al 1999;Wood et al 1999;Yeh and Hsu 2002;Karouna-Renier et al 2003;Chang 2005;Mahroof et al 2005). The differential expression has been studied during events that involve morphological changes in organisms such as gametogenesis, embryogenesis, and metamorphosis (Feder and Hofmann 1999).…”
Section: Introductionmentioning
confidence: 99%